Recommendations regarding splenectomy in hereditary hemolytic anemias - Iolascon, A; Andolfo, I; Barcellini, W; Corcione, F; Garçon, L; De Franceschi, L; Pignata, C; Graziadei, G; Pospisilova, D; Rees, DC; de Montalembert, M; Rivella, S; et al. (Ferrata Storti Foundation, 2017)
Hereditary hemolytic anemias are a group of disorders with a variety of causes, including red cell membrane defects, red blood cell enzyme disorders, congenital dyserythropoietic anemias, thalassemia syndromes and hemoglobinopathies. As damaged red blood cells passing through the red pulp of the spleen are removed by splenic macrophages, splenectomy is one possible therapeutic approach to the management of severely affected patients. However, except for hereditary spherocytosis for which the effectiveness of splenectomy has been well documented, the efficacy of splenectomy in other anemias within this group has yet to be determined and there are concerns regarding short- and long-term infectious and thrombotic complications. In light of the priorities identified by the European Hematology Association Roadmap we generated specific recommendations for each disorder, except thalassemia syndromes for which there are other, recent guidelines. Our recommendations are intended to enable clinicians to achieve better informed decisions on disease management by splenectomy, on the type of splenectomy and the possible consequences. As no randomized clinical trials, case control or cohort studies regarding splenectomy in these disorders were found in the literature, recommendations for each disease were based on expert opinion and were subsequently critically revised and modified by the Splenectomy in Rare Anemias Study Group, which includes hematologists caring for both adults and children.